Testing for a Debt‐Threshold Effect on Output Growth1. (30th August 2017) - Lee, Sokbae; Park, Hyunmin; Seo, Myung Hwan; Shin, Youngki
Abstract: Using the Reinhart–Rogoff dataset, we find a debt threshold not around 90 per cent but around 30 per cent, above which the median real gross domestic product (GDP) growth falls abruptly. Our work is the first to formally test for threshold effects in the relationship between public debt and median real GDP growth. The null hypothesis of no threshold effect is rejected at the 5 per cent significance level for most cases. While we find no evidence of a threshold around 90 per cent, our findings from the post‐war sample suggest that the debt threshold for economic growth may exist around a relatively small debt‐to‐GDP ratio of 30 per cent. Furthermore, countries with debt‐to‐GDP ratios above 30 per cent have GDP growth that is 1 percentage point lower at the median.